6
Q:

# If

 A) a=-11,b=-6 B) a=-11,b=6 C) a=11,b=-6 D) a=11,b=6

Explanation:
Q:

If (89)2 is added to the square of a number, the answer so obtained is 16202. What is the (1/26) of that number?

 A) 5.65 B) 2.7 C) 3.5 D) 6.66

Explanation:

Let the number is = x

(89)2 + x2 = 16202

x2 = 8281

x = 91

=> (1/26) of 91 = 3.5

10 430
Q:

What should come in place of x in the following equation?

 A) 13 B) 12 C) 17 D) 16

Explanation:

Then x2 = $\sqrt{162}x\sqrt{128}$

= Sqrt of 82 x 62 x 32

= 8 x 6 x 3

x2  = 144.

x  = 12.

5 398
Q:

Find the value of $\sqrt{\frac{\mathbf{1}\mathbf{.}\mathbf{21}\mathbf{x}\mathbf{0}\mathbf{.}\mathbf{9}}{\mathbf{1}\mathbf{.}\mathbf{1}\mathbf{x}\mathbf{0}\mathbf{.}\mathbf{11}}}$?

 A) 0 B) 1 C) 3 D) 5

Explanation:

Given   $\sqrt{\frac{1.21x0.9}{1.1x0.11}}$

$\sqrt{\frac{1.21x100x0.9x10}{1.1x10x0.11x100}}$

$\sqrt{9}$

= 3.

5 648
Q:

If  then find the value of ${\mathbit{x}}^{\mathbf{3}}\mathbf{-}\mathbf{6}{\mathbit{x}}^{\mathbf{2}}\mathbf{+}\mathbf{6}\mathbit{x}$ ?

 A) 1 B) 2 C) 3 D) 4

Explanation:

Given that

So x - 2 =

Now cubing on both sides, we get

=>

Therefore,

5 507
Q:

If

 A) 3/4 B) 4/3 C) 3/5 D) 5/3

Explanation:

By simplifying, we get 4/3

3 1028
Q:

If x =

 A) 3sqrt{3} B) 8sqrt{3} C) 14 D) 14+8sqrt{3}

Explanation:

31 1623
Q:

 A) 3 B) 3sqrt{2} C) 6 D) None of these

Explanation:

13 1545
Q:

$\left[\frac{3\sqrt{2}}{\sqrt{6}-\sqrt{3}}-\frac{4\sqrt{3}}{\sqrt{6}-\sqrt{2}}-\frac{6}{\sqrt{8}-\sqrt{12}}\right]=?$

 A) sqtr{3}-sqrt{2} B) sqtr{3}+sqrt{2} C) 5sqrt{3} D) 1

Explanation:

Given Exp = $\frac{3\sqrt{2}}{\sqrt{6}-\sqrt{3}}×\frac{\sqrt{6}+\sqrt{3}}{\sqrt{6}+\sqrt{3}}-\frac{4\sqrt{3}}{\sqrt{6}-\sqrt{2}}×\frac{\sqrt{6}+\sqrt{2}}{\sqrt{6}+\sqrt{2}}-\frac{6}{2\left(\sqrt{2}-\sqrt{3}\right)}$

$\frac{3\sqrt{2}\left(\sqrt{6}+\sqrt{3}\right)}{6-3}-\frac{4\sqrt{3}\left(\sqrt{6}+\sqrt{2}\right)}{6-2}+\frac{3}{\left(\sqrt{3}-\sqrt{2}\right)}×\frac{\left(\sqrt{3}+\sqrt{2}\right)}{\left(\sqrt{3}+\sqrt{2}\right)}$

$\sqrt{2}\left(\sqrt{6}+\sqrt{3}\right)-\sqrt{3}\left(\sqrt{6}+\sqrt{2}\right)+3\left(\sqrt{3}+\sqrt{2}\right)$

$\sqrt{12}+\sqrt{6}-\sqrt{18}-\sqrt{6}+3\sqrt{3}+3\sqrt{2}$

= $5\sqrt{3}$